TOPONYMS IN ECOLINGUISTICS: CONTRASTS AMONG DIFFERENT STRATEGIES OF NAMING PLACES IN IRAN AND BRAZIL - de Albuquerque, Davi Borges; Dastenaee, Mahnaz Talebi; Poshtvan, Hamideh (Revista de Letras, 2018)
Ecolinguistics and Toponymy are both marginal to General Linguistics. On one hand, the main contribution that Toponymy can provide is the knowledge of interactions between human and nature inside a linguistic environment. On the other hand, Ecolinguistics can offer distinct methodologies, tools of analysis, and conspicuous frameworks to placenaming. This work discusses theoretical and methodological issues regarding traditional Toponymy studies and the contributions that Ecolinguistics can present to this area. Furthermore, in order to clear up our assumptions on the relations between Ecolinguistics and Toponymy, we analyze data from two distinct places – two linguistic environments – one in Sergipe (Northeastern Brazil) and other in Gilan (Northern Iran), with different naming places mechanisms. The main mechanism is the influence of Territory physical traces on the place name, but there are several other, such as: the relations with the local inhabitants’ history or behavior, mental, nature or culture features as well. These naming places instruments reveal information about the Language, the People, and the Territory of those places. Keywords: Toponymy. Ecolinguistics. Ecosystemic Linguistics. Brazil. Iran.